1989
DOI: 10.2337/diacare.12.10.737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Once-a-Week Training Program on Physical Fitness and Metabolic Control in Children With IDDM

Abstract: To examine whether a physical activity program could improve physical fitness and glycemic control, 32 children and adolescents with insulin-dependent diabetes mellitus (IDDM) were examined before the program and 3 mo later. Fifty percent of the subjects (n = 16) participated in the training for 1 h/wk (exercise group), whereas the remaining subjects were engaged in nonphysical activities for an equal amount of time (nonexercise group). Age of the subjects ranged from 8.2 to 16.9 yr, (mean 11.9 yr), with mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 7 publications
0
56
0
1
Order By: Relevance
“…56,58,59,73,81,83,84,87,92,93,95,96,98,[102][103][104][105][106][107][108][109][111][112][113][117][118][119][120][121]126,127,131,133 Of the remaining studies, the interventions took place in family units, 59,60,97,124,129,134 in a mixture of group and individual settings, 94,[114][115][116]130 in some other arrangement or the details were not provided. 57,89,91,101,128 Of the 13 individual-based interventions, eight studies included a CG (five were RCTs and three involved a non...…”
Section: Individual Versus Group Educationmentioning
confidence: 99%
“…56,58,59,73,81,83,84,87,92,93,95,96,98,[102][103][104][105][106][107][108][109][111][112][113][117][118][119][120][121]126,127,131,133 Of the remaining studies, the interventions took place in family units, 59,60,97,124,129,134 in a mixture of group and individual settings, 94,[114][115][116]130 in some other arrangement or the details were not provided. 57,89,91,101,128 Of the 13 individual-based interventions, eight studies included a CG (five were RCTs and three involved a non...…”
Section: Individual Versus Group Educationmentioning
confidence: 99%
“…Several have shown reduced insulin secretion and hypoglycaemia but little reduction in HbA1c, [16][17][18] although when activity was stratified according to participation, metabolic control was significantly better among diabetic subjects participating frequently (at least 11 of 13 sessions), regardless of the type of activity. 19 More recently a study of 61 subjects with type 1 diabetes showed that modest changes in exercise and diet were suYcient to improve measures of glycaemic control and lipoprotein mediated risk of coronary heart disease. 20 In addition, some evidence suggests that the timing of exercise is an important factor, with regular postprandial exercise improving long term blood glucose control.…”
Section: Risks Of Exercise In Type 1 Diabetesmentioning
confidence: 99%
“…Studies on type 1 diabetes that have estimated glycaemic control through fasting blood glucose have also failed to show a consistent benefit [21,31,33,34]. Predictably, however, these studies demonstrated that blood glucose decreases (without hypoglycaemia) around the time of exercise [35,36], as it does in healthy individuals [37].…”
Section: Physical Activity Improves Fitness In Patients With Type 1 Dmentioning
confidence: 99%